Isolation of microalgae from antarctic soil - Zainal Abidin, Zaima Azira; Zahri, Nur Fazilah; Zainuddin, Zarina (Zibeline International Publishing, 2022)
Microalgae are unicellular photosynthetic microorganisms which are able to survive in extreme environmental conditions, specifically low temperature, high evaporation rates as well as low water availability. Polar microalgae from the Antarctic region have received attention from researchers due to their special adaptations for surviving in extremely cold environments and being isolated from various types of samples. Four Antarctic soil samples were used on this study namely-Sample A, Sample B, S18 and S30. All soil samples were subjected to serial dilution and spread on BBM followed by 3 weeks incubation at 25oC with periodic light. Only soil sample S30 showed positive microalgae growth after additional 3 weeks incubation period. Consequently, soil sample S30 was proceeded to isolation of microalgae using BBM, 3NBBM+V, JM and MWC media. Observable growth of green microalgae could only be obtained using 3N-BBM+V and JM media. Moreover, 3N-BBM+V medium successfully produced the highest number of microalgae colonies recovered from Antarctic soil sample. Isolation of microalgae from Antarctic provides resources for various industrial and commercial applications.